2021
DOI: 10.1186/s13063-021-05432-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture based on acupoint combination theory for irritable bowel syndrome: a study protocol for a multicenter randomized controlled trial

Abstract: Background Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder characterized by abdominal pain, diarrhea or constipation, and changes in defecation patterns. No organic disease is found to explain these symptoms by routine clinical examination. This study aims to investigate the efficacy and safety of acupuncture therapy for IBS patients compared with those of conventional treatments. We also aim to identify the optimal acupoint combination recommended for IBS and to clarify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous studies have confirmed that acupuncture has a significant effect on regulating abnormal gastrointestinal motility and is a cost-effective and safe therapy (4,5). Although an increasing number of randomized controlled trials report the efficacy of acupuncture for gastrointestinal disorders, especially for irritable bowel syndrome (IBS), of which pathophysiology shows gastrointestinal motility dysfunctions (5). There is no study using acupuncture for intestinal spasms in the process of colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that acupuncture has a significant effect on regulating abnormal gastrointestinal motility and is a cost-effective and safe therapy (4,5). Although an increasing number of randomized controlled trials report the efficacy of acupuncture for gastrointestinal disorders, especially for irritable bowel syndrome (IBS), of which pathophysiology shows gastrointestinal motility dysfunctions (5). There is no study using acupuncture for intestinal spasms in the process of colonoscopy.…”
Section: Introductionmentioning
confidence: 99%